(untitled) (Research, Society and Development, 2023)
This article aimed to carry out an analysis of the impacts of the Covid-19 pandemic on the lives of Brazilian farmers and family producers. The method used was a literature review. To search for papers, descriptors were used in order to cover aspects related to the dimensions of production, family income, credit and emergency aid. The results of this study show that the pandemic negatively impacted small rural producers in a multidimensional way: production, income and credit. In general, it can be seen that the sector of family production and agricultural marketing were greatly affected, with significant economic losses, much more intense in the most vulnerable families. As an alternative to overcome the marketing difficulties imposed by the pandemic, farmers sought new markets to continue to serve consumers and sell production that has been stopped. Regarding the impacts on credit, the divisions of producers and family farmers were extended, however the greatest impact was on the interest charged on Pronaf and the amount available for credit much lower than that destined to large producers. Unfortunately, it is known that, regardless of the pandemic, family farmers are not highly recognized in Brazil in terms of public policies, as can be seen in various analyses, whether social, statistical, legal or even economic. Added to this, there are recent movements of a political nature that aim to further deepen its obstacles.